Detection System for Threats of the Presence of Hazardous Substance in the Environment - Sovetov, B. Ya; Tatarnikova, T. M.; Cehanovsky, V. V. (2019 XXII International Conference on Soft Computing and Measurements (SCM), 2019)
The paper proposes the new solution for building a threat detection system for the spread of hazardous substances in the environment. The detection system is an all-around, autonomous solution that ensures the safety of human life and activity. Complexity and autonomy is realized by choosing the platform of the Internet of things technology and the neural network that solves the problem of recognizing threats.